Emergence of KRAS mutations and acquired resistance to anti-EGFR therapy in colorectal cancer - Misale, Sandra; Yaeger, Rona; Hobor, Sebastijan; Scala, Elisa; Janakiraman, Manickam; Liska, David; Valtorta, Emanuele; Schiavo, Roberta; Buscarino, Michela; Siravegna, Giulia; Bencardino, Katia; Cercek, Andrea; et al. (Nature (London), 2012)
Molecular alterations in KRAS are associated with acquired resistance to anti-epidermal growth factor receptor (EGFR) treatment in colorectal cancer; resistant mutations can be identified in the blood of patients, months before clinical evidence of disease progression. Acquired resistance in anti-EGFR therapy Antibodies targeting epidermal growth factor receptor (EGFR) have become an established treatment for colorectal cancer, but they are contraindicated in patients carrying mutations in the KRAS oncogene. Drug resistance can also arise in initially responsive patients, and two papers in this issue of Nature present unequivocal evidence that mutations in KRAS underlie acquired resistance to anti-EGFR antibodies in many patients and that KRAS mutations can be detected in the serum of patients before the clinical emergence of resistance and relapse. Misale et al . show in cell-line models that KRAS mutations can confer resistance to cetuximab. And in colorectal cancer patients treated with cetuximab or panitumumab, resistance is associated with KRAS mutations selected from pre-existing subclones or acquired during treatment. Diaz et al . also find KRAS mutations accumulating in patients becoming resistant to panitumumab. Their mathematical models suggest that KRAS mutations pre-existed in tumour cells before therapy, which may explain why clinical recurrence is usually seen after about six months of treatment, by which time the resistant subpopulations of tumour cells with KRAS mutations has expanded. The apparent inevitability of resistance suggests that combinations of drugs targeting more than one oncogenic pathway will be needed if resistance is to be avoided. A main limitation of therapies that selectively target kinase signalling pathways is the emergence of secondary drug resistance. Cetuximab, a monoclonal antibody that binds the extracellular domain of epidermal growth factor receptor (EGFR), is effective in a subset of KRAS wild-type metastatic colorectal cancers 1 . After an initial response, secondary resistance invariably ensues, thereby limiting the clinical benefit of this drug 2 . The molecular bases of secondary resistance to cetuximab in colorectal cancer are poorly understood 3 , 4 , 5 , 6 , 7 , 8 . Here we show that molecular alterations (in most instances point mutations) of KRAS are causally associated with the onset of acquired resistance to anti-EGFR treatment in colorectal cancers. Expression of mutant KRAS under the control of its endogenous gene promoter was sufficient to confer cetuximab resistance, but resistant cells remained sensitive to combinatorial inhibition of EGFR and mitogen-activated protein-kinase kinase (MEK). Analysis of metastases from patients who developed resistance to cetuximab or panitumumab showed the emergence of KRAS amplification in one sample and acquisition of secondary KRAS mutations in 60% (6 out of 10) of the cases. KRAS mutant alleles were detectable in the blood of cetuximab-treated patients as early as 10 months before radiographic documentation of disease progression. In summary, the results identify KRAS mutations as frequent drivers of acquired resistance to cetuximab in colorectal cancers, indicate that the emergence of KRAS mutant clones can be detected non-invasively months before radiographic progression and suggest early initiation of a MEK inhibitor as a rational strategy for delaying or reversing drug resistance.